Enzymatic Production of Prebiotic Oligosaccharides - Vera-Vera, C (Elsevier Ltd, 2021)
Prebiotics are health promoting functional food ingredients. Main prebiotics are non-digestible oligosaccharides (NDOs), which are extracted from natural sources or enzymatically synthesized. The presence of equally reactive hydroxyl groups in carbohydrates makes the chemical synthesis of NDOS quite complex, so their enzymatic production is the preferred choice at large scale. The impressive advances in enzyme biocatalysis has allowed the development of robust biocatalysts which are compatible with their use under the rather harsh conditions usually required for the reactions of synthesis. In fact, nowadays several NDOs are being produced enzymatically at industrial level. In this article, the use of glycoside-hydrolases and glycosyltransferases for commercial NDOs production is reviewed. © 2020 Elsevier Ltd